'Eisenbergiella massiliensis', a new species isolated from human stool collected after bariatric surgery. (September 2016) - Togo, A.H.; Khelaifia, S.; Bittar, F.; Maraninchi, M.; Raoult, D.; Million, M.
Abstract: We report the principal characteristics of ' Eisenbergiella massiliensis ' sp. nov. strain AT11 (CSURP = P2120, DSM = 101499) that was isolated from a stool sample collected after bariatric surgery of a 56-year-old obese French woman.